Neuroprotective Effects of Salvia Hydrangea Extract through Dietary Uptake in Amyloid Beta-injected Rats - Kheradmand, Afshin; Fallah, Shayan; Sadat-Shirazi, Mitra-Sadat; Ashabi, Ghorbangol; Khalifeh, Solmaz; Zare, Nayereh (Archives of Advances in Biosciences, 2024)
Introduction: Alzheimerʼs disease (AD) has been identified as a progressive memory and cognitive impairment. Some Salvia species are suggested by certain studies for the management of mild to moderate AD. We aimed to evaluate the anti-inflammatory, antioxidant, and anti-apoptotic effects of S. hydrangea on amyloid beta-injected rats. Materials and Methods: Rats were pretreated with S. hydrangea for 10 days before amyloid beta (Aβ) injection. Western blotting techniques were used to evaluate protein level of γ-glutamyl cysteine synthetase (γ-GCS), Tumor Necrosis Factor α (TNF-α) and Interleukin-6 (IL-6) in two brain regions: hippocampus and frontal cortex. Results: Current data show that S. hydrangea extract increased γ-GCS protein levels in amyloid beta injected rats, and pretreatment with S. hydrangea increased it further. Besides, S. hydrangea decreased protein levels of TNF-α and IL-6 in amyloid beta injected rats. Conclusion: Based on the decreased levels of IL-6, TNF-α, and the increased levels of γ-GCS, it is suggested that the use of S. hydrangea could be protective in neurodegenerative diseases.